Optimization of PTNBH Asset Utilization (ITS case study from BLU to PTNBH) - Hanoraga, Tony; Trisyanti, Umi (Indonesian Journal of Development Studies, 2020)
In 2015 after ITS was designated as a Legal Entity State University with Government Regulation Number 54 of 2015 concerning ITS Statutes, at ITS there was a change in authority to manage separated assets. This authority includes managing, deleting and utilizing assets. This study aims to determine the forms of asset utilization at ITS, who has the authority to grant permits and implement assets utilization at ITS and how to optimize the utilization of ITS assets. This research is normative research. Research that will examine based on the concepts of asset utilization and the applicable positive legal rules. The form of asset utilization that can be carried out by PTBH is leasing, borrowing and using, cooperation in utilization and building handover or building to deliver. The authority to use assets at ITS lies with the Chancellor as the manager of the goods, WR2 as the user of the goods, and several parties such as the DKPU as the power of the goods user. Optimizing the utilization of ITS assets is the concept of utilizing assets to achieve the maximum profit or benefit by not disturbing the duties and functions of the assets for ITS and not violating applicable regulations.